2013
DOI: 10.1111/clr.12093
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial adhesion on the titanium and zirconia abutment surfaces

Abstract: There was a significant difference in the total bacterial count between the three groups. CPT presented the higher mean counts, followed by MPT and Zc. CPT group also showed a higher mean incidence of species than MPT and Zc. The anterior or posterior region of disks placement did not show significant differences in relation to bacterial adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 43 publications
4
104
2
6
Order By: Relevance
“…However, conflicting opinions exist on biofilm formation among different types of materials [15,7275]. Titanium and zirconia are hydrophobic materials.…”
Section: Surface Characteristics Of Abutments Implantsmentioning
confidence: 99%
“…However, conflicting opinions exist on biofilm formation among different types of materials [15,7275]. Titanium and zirconia are hydrophobic materials.…”
Section: Surface Characteristics Of Abutments Implantsmentioning
confidence: 99%
“…Conversely, in other study, the same authors [34] concluded that there was a significant difference: titanium presented most bacteria and also showed a higher mean incidence of species than did zirconia.…”
Section: Modelmentioning
confidence: 77%
“…Five were clinical reports [2,6,8,18,24] and 35 were papers on PEEK surface treatments [13][14][15][16][17] how the bioactivity of PEEK can be improved [1,21]; the characteristics of CFR-PEEK [3,7,[19][20]; the biocompatibility of PEEK [5]; PEEK applications [4,8,[10][11]30]; PEEK biofilm formation [22,[31][32][33][34], PEEK as an abutment material and as an implant material [12,23,[25][26][27][28][29]35,40] and the use of CAD-CAM with PEEK [36][37][38][39]. …”
Section: Literature Search and Resultsmentioning
confidence: 99%
“…The results were of 12.1% and 19.3% for zirconia oxide and titanium, respectively . Another study analyzing biofilm formation, reported a higher bacterial mean count over titanium samples than zirconia samples . Although bacterial count was not evaluated in the present evaluation, our clinical observations and results of gingival and plaque indexes evidenced significantly low plaque accumulation.…”
Section: Discussionmentioning
confidence: 99%